Factors Associated with Chronic Obstructive Pulmonary Diseases in Nepal: Evidence from a Nationally Representative Population-Based Study - Karki, Khem Bahadur (Int J Chron Obstruct Pulmon Dis, 2021)
BACKGROUND: The Global Burden of Diseases Study 2017 predicted that chronic obstructive pulmonary disease (COPD) is the second leading cause of death, the fourth leading cause of premature death, and the third cause for DALYs lost in Nepal. However, data on the population-based prevalence of COPD in Nepal are very limited. This study aims to assess the prevalence of COPD and factors associated with the occurrence of COPD in Nepal. METHODS: From a nationally representative, population-based cross-sectional study on chronic non-communicable diseases, the prevalence of COPD and its associated factors was determined. Of 12,557 participants aged over 20 years, 8945 participants completed a questionnaire and spirometry. Eligible participants were also asked to answer a COPD diagnostic questionnaire for screening COPD cases, and if needed underwent pre-bronchodilator and post-bronchodilator spirometry. COPD was defined as a post-bronchodilator FEV1/FVC (forced expiratory volume in 1 s/forced vital capacity) ratio of <0.70. Multivariate logistic regression was performed to identify factors associated with COPD. Sampling weights were used for all data analyses. RESULTS: The prevalence of COPD in Nepal was 11.7% (95% CI: 10.5% to 12.9 %), which increased with age, and higher in those with a low educational level, those who had smoked ≥50 pack-years, persons having a low body mass index (BMI), and residents of Karnali province. Multivariate analysis revealed that being aged 60 years and above, having a low BMI, low educational status, having smoked more than 50 pack-years, provincial distribution, and ethnicity were independent predictors of COPD. CONCLUSION: COPD is a growing and serious public health issue in Nepal. Factor such as old age, cigarette smoking, low educational attainment, low BMI, ethnicity, and locality of residence (province-level variation) plays a vital role in the occurrence of COPD. Strategies aimed at targeting these risk factors through health promotion and education interventions are needed to decrease the burden of COPD.